Big little spies - Davis, Krista (Davis, Krista. Paws and claws mysteries., 2021)
"The ladies of the Wagtail Animal Guardians, WAG for short, are in town for a pet adoption charity ball, and Holly is making sure to roll out the red carpet for her special guests. She and her furry best friend Trixie are busy keeping the WAG ladies happy and preparing for the ball when they learn that a retired judge has lost his prized pup. The venerable citizen has hired a pet detective who has some personal ties to Holly's new guests. His presence ruffles some feathers, and when the PI is found DOA not long before the ball, Holly wonders if one of the WAG ladies had a motive for murder. To make matters worse, some pet-loving guests of the ball nearly suffer the same deadly fate. Holly and Trixie will have to sniff out the clues and leash a callous killer before they strike again." -- Amazon.